ANALISIS PENERAPAN MODAL INTELEKTUAL PADA BADAN USAHA MILIK DAERAH PT. SUBANG ENERGI ABADI - Kharisma Sutanti; Nunung Juliawati; Panji Agnyoto; Fajar Meiyanti (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This research aims to analyze the application of intellectual capital at BUMD. If BUMD had applied intellectual capital it would have had a better effect on the company/BUMD's performance so that its manufacturing purposes could be met. The research was intended to identify the application of intellectual capital on the BUMD PT. SEA. The method used by the researcher is a deep-seated interview with a qualitative approach, with data obtained from live interviews with the staff of BUMD PT. SEA. The results show that the application of intellectual capital and its components of human capital, capital, and relational capital at the top of the world bank was well implemented by the BUMD PT. SEA. The results of the interview revealed that the BUMD PPN had adopted the intellectual capital and its indictments, such as tacit knowledge, explicit knowledge, the training programs that the BUMD knowledge adopted, the corporate image, the organizational concept, and documentation that the BUMD adopted. Its relational customer capital and its indictments like a long-term contract, Customer satisfaction, customer profile, and contract renewal have already existed and have already been implemented by BUMD PT SEA.